Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve the system by the elimination method. Check your work.

[tex]
\begin{array}{l}
2a + 3b = 6 \\
5a + 2b - 4 = 0
\end{array}
[/tex]

Make sure there are no spaces in your answer. Include a comma in your answer.

ANSWER: [tex]$\square$[/tex]


Sagot :

To solve the system of equations by the elimination method, follow these steps:

[tex]\[ \begin{array}{l} 2a + 3b = 6 \quad \text{(1)} \\ 5a + 2b - 4 = 0 \quad \text{(2)} \end{array} \][/tex]

First, rearrange the second equation to match the form of the first equation:

[tex]\[ 5a + 2b = 4 \quad \text{(3)} \][/tex]

Now, we have the system:

[tex]\[ \begin{array}{l} 2a + 3b = 6 \quad \text{(1)} \\ 5a + 2b = 4 \quad \text{(3)} \end{array} \][/tex]

The goal is to eliminate one of the variables. To do this, we need the coefficients of either [tex]\(a\)[/tex] or [tex]\(b\)[/tex] to be the same in both equations. Let's eliminate [tex]\(b\)[/tex].
We will multiply equation (1) by 2 and equation (3) by 3 to make the coefficients of [tex]\(b\)[/tex] equal:

[tex]\[ 4a + 6b = 12 \quad \text{(4)} \][/tex]
[tex]\[ 15a + 6b = 12 \quad \text{(5)} \][/tex]

Next, we subtract equation (4) from equation (5):

[tex]\[ (15a + 6b) - (4a + 6b) = 12 - 12 \][/tex]
[tex]\[ 11a = 0 \][/tex]
[tex]\[ a = 0 \][/tex]

Now we know [tex]\(a = 0\)[/tex]. To find [tex]\(b\)[/tex], substitute [tex]\(a = 0\)[/tex] back into either original equation. Let's use equation (1):

[tex]\[ 2(0) + 3b = 6 \][/tex]
[tex]\[ 3b = 6 \][/tex]
[tex]\[ b = 2 \][/tex]

So the solution to the system of equations is [tex]\(a = 0\)[/tex] and [tex]\(b = 2\)[/tex].

To check the solution, substitute [tex]\(a = 0\)[/tex] and [tex]\(b = 2\)[/tex] back into the original equations:

For equation (1):

[tex]\[ 2(0) + 3(2) = 6 \][/tex]
[tex]\[ 6 = 6 \quad \text{(True)} \][/tex]

For equation (2):

[tex]\[ 5(0) + 2(2) - 4 = 0 \][/tex]
[tex]\[ 4 - 4 = 0 \][/tex]
[tex]\[ 0 = 0 \quad \text{(True)} \][/tex]

Both equations are satisfied with [tex]\(a = 0\)[/tex] and [tex]\(b = 2\)[/tex].

Thus, the answer is:
[tex]\[ \boxed{0,2} \][/tex]